STUDENTS’MOTIVATION TOWARDS ONLINE LEARNING IN THE FOURTH SEMESTER DURING COVID-19 PANDEMIC - Hesthi Herusatoto; Sri Endah Setia Rini; Ayu Natalia Wulandari (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2022)
Online learning during the Covid-19 pandemic that has been going on for more than 4 semesters or 2 years in Indonesia might have made students feel no longer motivated to participate in online meetings. Problems with the internet and technology, heavy workload, as well as lack of student-student and student-teacher interactions have become the main reasons for students feeling demotivated as revealed by previous studies. This research was to examine the motivation of college students in STBA LIA Yogyakarta in participating in online learning on Zoom and to investigate the reasons that might demotivate them to join Zoom meetings. Questionnaires and a forum group discussion (FGD) were carried out to collect data. Descriptive analytical method was then used to analyze their responses to questions concerning motivation in the survey, and a cross tabulation analysis was to analyze the relationship between students who were demotivated and the reasons why they were less motivated towards Zoom meetings. The results indicated that most of the respondents were still motivated to take online lectures. Yet, such reasons as problems with the internet connectivity, the lecturers, and the classmates also contributed to make students less motivated.